Calcários calcítico e dolomítico e alterações nos tributos de solos e plantas sob sistema de plantio direto - Miotto, Alcione (2009)
The lime application decrease soil acidity and increase the exchangeable calcium (Ca) and magnesium (Mg) level. calcitic and dolomitic limes cannot present the same efficiency in soil acidity correction and since it can enlarge or narrow the Ca:Mg soil relationship, it also may cause nutritional problems to the plants or even to harm their development. Four experiments were carried out: one in a greenhouse and three in field conditions. The greenhouse experiment aimed to quantify the calcium and magnesium supply to the soybean roots cultivated in soil with Mg growing saturations in CEC pH 7. A no-liming Oxisoil was used; it was collected right on the 0-20 cm layer, dry, grind and sieved through 2 mm. Then CaCO3 or the CaCO3+MgCO3 mixture was applied aiming at elevating the water pH up to 6, making possible Mg growing saturations in CEC pH 7. The soil was conditioned in pots and, after incubation, cultivated with soybean for a period of 80 days. During the experiment, dry matter production evaluations, content and accumulation of calcium and also magnesium on tissue were carried out as well as the supply of those to the roots. The three field experiments were accomplished with two main objectives: a) to evaluate the resulting alterations of the calcitic and dolomitic limestone proportions application in the soils exchangeable level of calcium and magnesium and also to verify their effects in plants nutrition; and b) to evaluate the efficiency of calcitic and dolomitic limestone with superficial and incorporate application in soil acidity correction and in the productivity of crops in no-tillage. These experiments were carried in october 2004, in Rio Grande do Sul state different physiographic areas through no-tillage and cultivated with annual crops. The treatments consisted in an enough dose of calcitic and dolomitic limestone application proportions to elevate the pH in water up to 6, applied in the surface or incorporated. The production of black oats dry matter and soybean, wheat, canola grains yeild, and content of Ca and Mg in the vegetable tissue of these cultures were evaluated. After 42 months from the treatment application, soil samples were collected in the layers of 0-5; 5-10; 10-15; 15-20 and 0-10 cm and then the exchangeable level of Ca, Mg and Al, pH in water and saturation for bases were determined. The results show that the Ca and Mg plants content alterations are due to the magnitude of the supply of those to the roots more than to the Ca:Mg ratio. The limestone considerably alter the level of Ca and exchangeable Mg and also the Ca:Mg ratio of the soil, what does not provoke nutritional problems to the cultures as long as the soil tenors are enough, the interaction among both cations in the plant absorption is of low intensity or it does even exist. The calcitic and dolomitic limestone present the same agronomic efficiency in the acidity correction and the crops productivity is not affected by the type of applied limestone.